Karakteristik Hasil Fermentasi Buah Annona montana Menggunakan Saccharomyces cereviceae - Ambar Fidya Sari; Kiki Mirza Amalia; Jefri Nur Rochim (Jurnal Ilmu Pangan dan Hasil Pertanian, 2020)
Soursop mountain (Annona montana Macf) is a genus of Annonaceae, which contains metabolite compounds and antioxidant activity. Mountain soursop fermentation process is carried out with the addition of yeast Saccharomyces cereviciae which can convert carbohydrates into ethanol and organic acid.. The study is aimed at knowing the impact of the duration of the fermentation on the Soursop mountain on physical and chemical characteristics as a natural preservative. The study involves three stages, beginning with the production of mountain-source-juice, then fermentation, and testing of physical characteristics involving organoleptic (colour, aroma, taste, and texture), pH, and viscosity, whereas on the chemical characteristic that is total acid. Research data is analyzed by the One Way Anova method when there is a valid influence followed by the Post Hoc Tukey at real levels α=5%. Changes in physical and chemical grade values include organoleptic (yellow whiteness, aroma scent of the tape, a slightly thick liquid texture (soft) and no gloating, a very sour taste, a 3,86 pH value, a viscosity 583,33 cp, and a total acetate acid 0,4281%.